2008
DOI: 10.1007/s12072-008-9098-6
|View full text |Cite
|
Sign up to set email alerts
|

A 7-day profile of oxidative stress and antioxidant status in patients with acute liver failure

Abstract: A high level of systemic oxidative stress exists in ALF, with depletion of antioxidant reserves. Further studies are needed to define the clinical correlation of the large pro-oxidant burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The release of necrotic products into the circulation might trigger a systemic inflammatory response . In patients with acute liver failure, a high level of oxidative stress is observed . Moreover, a novel and accurate marker of oxidative stress, advanced oxidation protein, has been shown to participate in activation of monocytes and neutrophils, which aggravate inflammation and induce liver injury via mitochondrial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…The release of necrotic products into the circulation might trigger a systemic inflammatory response . In patients with acute liver failure, a high level of oxidative stress is observed . Moreover, a novel and accurate marker of oxidative stress, advanced oxidation protein, has been shown to participate in activation of monocytes and neutrophils, which aggravate inflammation and induce liver injury via mitochondrial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia et al . observed patients with acute liver failure for about 7 days and found that there was a high level of oxidative stress in these patients 22 . Emerging data suggested that acetaminophen (APAP)‐induced hepatic failure was associated with mitochondrial dysfunction due to oxidative stress, 23 which aggravated inflammation and induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of the liver to fulfill its normal physiological function can result in acute or chronic hepatic failure. Acute hepatic failure (AHF) is hallmarked by a rapid and immense necrosis and hepatocyte apoptosis . Underlying causes of AHF are mainly drug‐induced liver toxicity or viral hepatitis .…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 99%
“…Oxidative stress not only damages cellular components like DNA, proteins or lipids, but also causes the release of proinflammatory cytokines leading to hepatic fibrosis, inflammation and cirrhosis . The dying hepatocytes are also a source of oxidative stress causing further destruction of hepatocytes and release of ROS, thus, establishing a vicious circle . In the various forms of liver disease, ROS are mainly produced in the mitochondria and endoplasmic reticulum by cytochrome P450 enzymes, a process occurring in hepatocytes, Kupffer cells and neutrophils (Fig.…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 99%